Analyzing Changes in Sport Activity Patterns Caused by the COVID-19 Pandemic: Focusing on the Sport Role of Sustainable Development Goals Related to Health and Well-being - Kisung Kwon; Jihun Kim (Korea Institute of Sport Science, 2022)
PURPOSE The United Nations (UN) has proposed 17 Sustainable Development Goals and has been extending its efforts to achieve them. Sport can be linked closely to the third goal, which is related to health and well-being. Therefore, this study aimed to explore and to analyze individual's changed sport activities during the COVID-19 pandemic, focusing on ways to achieve health and well-being related goals through sport. METHODS A qualitative research method was employed, and in-depth interview methods were used for data collection. For data analysis, categorization and itemization were used along with content analysis. RESULTS Looking at the derived results, in the context of an infectious disease such COVID-19, sport activity patterns have changed due to reasons such as stadiums or facilities, interpersonal reasons, fear, inconvenience, staying healthy, increase in leisure time, and individual preferences. CONCLUSIONS Due to the COVID-19 pandemic, the indicators of health and well-being related SDGs are exhibiting a downward trend. At this point, it is necessary to find a way to achieve the goal through sport that can participate voluntarily for the purpose of pursuing pleasure.